Alliance formation: A Study of the Malaysian Automobile Supporting Industry - Abdul Ghani, Ahmad Bashawir; Tull, Malcolm (Gadjah Mada International Journal of Business, 2010)
CompetitionÂ  inÂ  globalÂ  industriesÂ  isÂ  shiftingÂ  increasingly fromÂ  inter-firmÂ  rivalryÂ  toÂ  rivalryÂ  betweenÂ  networksÂ  ofÂ  firms. Strategies of individualÂ  firms are thus contingent on the degree of interdependence that exists between them and the parent firm in the network. The present study examines the effect of network affiliation on a member firmâs decision to enter a foreign market andÂ  internationalÂ  strategicÂ  allianceÂ  formation.Â  AffiliateÂ  firms have two options available to them: (1) enter into a competitive strategic alliance with a competitor or (2) enter into a symbioticstrategic alliance withÂ  the parent firm of the network organiza-tion.Â  We testedÂ  this assertionÂ  usingÂ  dataÂ  from archivalÂ  sources onÂ  sixty-fiveÂ  JapaneseÂ  automobileÂ  suppliersÂ  thatÂ  hadÂ  setÂ  up strategicÂ  alliancesÂ  inÂ  MalaysiaÂ  andÂ  thatÂ  belongedÂ  toÂ  various inter-organizationalÂ  networks.Â  ResultsÂ  indicateÂ  thatÂ  whenÂ  affili-ate firms are dependent on the parent firm, they prefer to form symbioticÂ  strategicÂ  alliances.Â  Conversely,Â  affiliateÂ  firmsÂ  prefer competitiveÂ  strategicÂ  alliancesÂ  withÂ  competitorsÂ  whenÂ  theyÂ  are notÂ  dependentÂ  onÂ  theÂ  parentÂ  firm. ALLIANCEÂ  FORMATIONA Study of the Malaysian Automobile Supporting IndustryKeywords: automobile industry; joint venture; mode of entry; networks; strategic alliances